CONSTITUTIONAL RIGHT TO NON-ADMITTANCE TO INTERFERE WITH THE EMPLOYEE’S INDIVIDUAL AND FAMILY LIFE - Вишновецька, Світлана Василівна; Вишновецький, Вадим Михайлович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: in the article the authors research the problems of ensuring constitutional right to prevent interference with the employee’s individual and family life. The views of scientists, the decisions of the Constitutional Court of Ukraine, the decisions of the European Court of Human Rights on understanding the personal and family life and the right to respect it are analyzed. Methods of research: general scientific and special methods are used in the work. Results: personal non-proprietary labour rights are defined. It is concluded that in the effective labour legislation there are no legal constructions to ensure the integrity of the employee’s personal life. Discussion: search for solutions to the problem of the limits of the permissibility of the employer to control and monitor the actions of employees during the working hours (tracking the Internet activity, e-mail of the employees) and the overall behaviour of the employees in and out of work places.